"Tell us this story from the beginning": genre, dialogue, and cultural translation in Thomas Stephens’s Kristapurāṇa - Royson, Annie Rachel (Nidān, 2019)
Missionary compositions from Portuguese Goa have often been read as colonial impositions in which the missionary spoke, and the convert merely listened. The present study is an attempt to locate "dialogue" as a critical aspect of cultural translation in Kristapurāṇa (1616), a seventeenth-century retelling of the Bible in the Marathi language. A close reading of select verses from Kristapurāṇa is undertaken to unravel the multiple layers of "dialogue" at work in the text. The dialogic nature of Kristapurāṇa is twofold: a) the conversational tone and development of the narrative through the question-answer format; and b) a more complex dialogic relationship where texts from diverse traditions such as the biblical and the purāṇic, "speak" to one another. Dialogue as a generic feature of purāṇic tradition, the question answer format of the Church’s catechism, and exchanges between missionaries and converts will be analyzed in this study in order to highlight the dialogic nature of cultural translation in Kristapurāṇa.